Sudut Pandang Aliran HumanistikTerhadap Model Pendidikan Andragogi - Bayu, Bayu (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2004)
In -general there are two understand that teaching pedagogy that is valid and andragogy . Andragogy understand is the place to study participants as "adult". Students are placed as the subject of the education system. Students as adults assumed to have the ability to plan wisely, choose materials that are able to analyze and useful. Function as a teacher is a facilitator and not dominator. Second is to understand the current debate that is still experiencing a little difficult to classified school in Indonesia understand which of the two. This cause's difficulties classification school is only based on the nature of education in the schools. 'Schools in Indonesia can be classified into a modern schoorthat is not doctrinaire, and based on skills